Microbiological contamination in IVF laboratories: A narrative review - Sudheer Singh; Nancy Nair; Akash More; Neeraj Vishwakarma; Avanti Kalbande (Asian Pacific Journal of Reproduction)
In vitro fertilization (IVF) is one of the most used assisted reproductive technology (ART) techniques today. However, the success of IVF procedures heavily relies on maintaining a sterile environment in laboratories. This narrative review examines the effects of microbiological contamination in IVF laboratories, exploring its sources, impacts on IVF outcomes, and preventive measures. We conducted a complete literature search using databases such as PubMed and Google Scholar, focusing on studies published within the last fifteen years. Our findings highlight that microbiological contamination can significantly impair embryo quality, reduce implantation and pregnancy rates, and increase the risk of miscarriage and infection. The review also discusses current best practices for contamination prevention and identifies areas for future research. This work emphasizes the critical importance of stringent sterility protocols in IVF laboratories and calls for continued vigilance and innovation in maintaining optimal conditions for assisted reproduction.